Application of Phosphate-Based Binders for the Stabilization and Solidification of Metal-Contaminated Soil: Mechanisms and Efficacy Evaluation - Shiliang Xu; Ayesha Imtiyaz Cheema; Yunhui Zhang; Bin Dong (Toxics)
At present, contamination due to toxic metals is a global concern. The management of problems caused by heavy metals relies on stabilization/solidification, which is the most effective technique for the control of metal pollution in soil. This study examined the immobilization efficiency of various phosphate-based binders (Na3PO4, Na2HPO4, NaH2PO4), in addition to ordinary Portland cement (OPC), MgO, and CaO, for the stabilization of multi-metal-contaminated soils. Moreover, this study focused on the leachability of copper, nickel, zinc, lead, cadmium, and manganese (Cu, Ni, Zn, Pb, Cd, Mn, respectively) over different time periods and with different concentrations. Batch leaching experiments were conducted to determine the leaching ratios and percentages of the various metal concentrations, along with measuring the pH values of the leachates. Our results indicate that the use of OPC was validated due to its superior immobilization performance across all metals present in the soil, but particularly with regard to metals in high concentrations. This was due to the formation of stable hydroxides and the high pH values, which assisted in abating the metals’ solubility. Additionally, phosphate-based binders, despite being environmentally favorable, were found to be less effective, particularly for Pb and Cu, and the leaching results exceeded non-hazardous waste limits. MgO showed reasonable immobilization results but was less effective compared to OPC; on the other hand, CaO exhibited increased leaching over time. Therefore, the present research serves primarily to highlight that OPC is more suitable for soil remediation at industrial sites and in the construction of infrastructure. Meanwhile, phosphate-based binders are shown to be more appropriate for eco-friendly, non-load-bearing applications.